The Legacy of Ricardo - Roberto Scazzieri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1987)
A characteristic feature of economic knowledge is that the contributions of distinguished economists of the past are often interpreted in alternative, and seemingly incompatible ways.
Keywords: 330